Strategiczne problemy zarządzania elastycznością firmowych systemów informacyjnych - Skwarnik, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The turbulent enterprise environment enforces adequate MIS changes. Without these modifications the efficiency of management processes and procedures may dramatically decrease. In this article we present MIS flexibility in the context of changes problem solution. First we discuss MIS flexibility phenomenon, presenting its essential elements. Next we propose MIS flexibility management as an advanced, organized form of information system changes preparation. We focus on strategic phase of these preparations, describing active, passive and mixed forms of flexibility strategy. Then we propose supplementary MIS flexibility specifications, related to flexibility resources, tools, skills, and methods. We analyse feasibility and usefulness of these specifications. As a conclusion we suggest conducting comprehensive and detailed MIS flexibility specifications research. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 103-111